Idiopathic hypogonadotropic hypogonadism in selective humangonadotropin deficiency in adult man: a case report - Volpi, R.; Ugolotti, M. C.; Carbucicchio, A.; Delsignore, R. (Acta Biomedica Atenei Parmensis, 2008)
We report a rare case of idiopathic hypogonadotropic hypogonadism in an adult male (31-jear-old), who underwent an endocrinological examination because of erectile dysfunction and suspected infertility. Laboratory data showed isolated gonadotropin deficiency. Magnetic resonance imaging (MRI) of the hypothalamic-pituitary unit showed no tumoral expansions. The patient was tested with gonadotropin releasing hormone (Gn-RH) (100 μg as an i.v. bolus injection). No significant LH and FSH responses were observed. Idiopathic hypogonadotropic hypogonadism is usually caused by hypothalamic lesions, however, since Gn-RH was unable to stimulate LH and FSH secretions, we supposed that our patient was affected by defective gonadotropin secretion at pituitary level.